Bacteria Producing Extended Spectrum β-lactamases (ESBLs) in Hospitalized Patients: Prevalence, Antimicrobial Resistance Pattern and its Main Determinants - Mehdi Yousefipour; Mehrnaz Rasoulinejad; Azar Hadadi; Negin Esmaeilpour; Alireza Abdollahi; Siroos Jafari; Atieh khorsand (Iranian Society of Pathology, 2019)
Background and Objective: There is a growing concern regarding the lack of new antibiotics, especially for multidrug-resistant bacteria that produce Extended Spectrum β-Lactamases (ESBLs). The present study aims to assess the prevalence of bacteria producing ESBLs, their antimicrobial resistance pattern, and its main determinants among hospitalized patients.Methods: The study population included 383 consecutive patients with a definitive diagnosis of urinary tract infection (UTI). All eligible subjects for the study had a positive culture for gram-negative microorganisms in urine specimens. ESBL producing isolates were characterized phenotypically for ESBL production using the double disc synergy test.Results: In total, 383 specimens were assessed, among which 212 (55.4%) were related to bacteria producing ESBLs (ESBL+). Of those with ESBL + infections, 65.5% were sourced from catheters (as hospital-associated UTIs), and 35.5% were categorized as community-associated UTIs. In the group consisting of bacteria producing ESBLs, the highest sensitivity was observed with Imipenem (72.2%), while the highest resistance was revealed with ceftriaxone (100%). Conclusion: We have shown that our community faces a high prevalence of bacteria producing ESBLs, mostly sourced from the catheterization of hospitalized patients. The highest bacterial sensitivity was observed with Imipenem, nitrofurantoin, and amikacin, while the highest resistance was found with ceftriaxone and cotrimoxazole, suggesting the ineffectiveness of using the two latter antibiotics for eradicating these bacterial infections. On the other hand, a history of urinary catheterization and previous hospitalization were two main determinants of their presence, a finding which emphasizes the importance of avoiding catheterization and hospitalization of patients with UTIs without proper indications.